The Aesthetic Management of a 180 Degree Rotated Maxillary Central Incisor With Two Root Canals- A Case Report - Shweta Jain; Praful Narang; Rohit Sharma; Vijay Agarwal (Journal of Clinical and Diagnostic Research, 2013)
The success of the root canal treatment is based on a thorough knowledge of the normal tooth, the root and the root canal morphology, which include variations. Tooth rotation is a common finding in the premolar-molar region, but a 180 degree rotation of the maxillary central incisor is extremely rare and it has not documented anywhere in the dental literature. This case report describes the aesthetic correction of a maxillary central incisor with a 180 degree rotation and two root canals.